Analysis and modeling of the cloud impairments of satellite-to-land mobile channel at Ku and Ka bands - Al-Saegh, Ali Mohammed; Sali, Aduwati; Ismail, Alyani; Jit Singh, Mandeep Singh (IEEE, 2014)
Cloud impairments have significant effect on signal propagated in the satellite to land stationary terminals channel at frequencies above 10 GHz. With the recent satellite to land mobile terminals network technologies and services that use these frequencies, there is a lack of channel impairments modeling and analysis for such type of link. This study presents a reliable channel model of satellite-to-land mobile terminals that consider dynamic cloudy weather impairments. The cloud’s dynamic parameters and their effect on the Rician factor are modeled. The model involves modules that design multipath signals, direct clear line-of-sight (LOS) normalized signals, and cloud impairments. Results show that a considerable change occurs in the performance of the signal propagated through the cloud. The change appears as deviations in the fade depth and the variance of the propagated signal in the link between the satellite and the land mobile terminals. The channel model is a realistic approach to the link characteristics, which satellite systems designers should consider when designing high data rate satellite systems.